Relationship between personality traits and reproductive choices among women attending the psychiatric clinic of a Nigerian Teaching Hospital - Mapayi, Boladale M.; Seun-Fadipe, Champion; Akinsulore, Adesanmi; Aloba, Olutayo O.; Oginni, Olukunle O.; Ugalahi, Theresa O. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2019)
Background: The study aimed to assess the relationship between personality traits and reproductive choices among women attending the psychiatric clinic at a Nigerian Teaching Hospital. Methods: The original study used a quasi-experimental pre-test post-test-controlled design though this article presents a cross sectional view of results. Two hundred females were recruited into the study. An interviewer-administered questionnaire was applied to the respondents which elicited information on background characteristics, baseline contraceptive indicators and personality traits. Data were analyzed using both descriptive and inferential methods. Results: The personality factors found to affect contraceptive use included high scores on Conscientiousness, Extraversion and Neuroticism, though only extraversion maintained this relationship on regression analysis. The personality factors found to affect pregnancy plan included high scores on Conscientiousness. Conclusions: This study showed a distinct relationship between specific personality traits and contraceptive use with neuroticism exhibiting a negative influence on use while conscientiousness exhibited a positive influence.